2011
DOI: 10.3727/096368910x543411
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of Intravenous Neural Stem Cell Delivery for Treatment of Neuroinflammatory Disease in Mice?

Abstract: While neural stem cells (NSCs) are widely expected to become a therapeutic agent for treatment of severe injuries to the central nervous system (CNS), currently there are only few detailed preclinical studies linking cell fate with experimental outcome. In this study, we aimed to validate whether IV administration of allogeneic NSC can improve experimental autoimmune encephalomyelitis (EAE), a well-established animal model for human multiple sclerosis (MS). For this, we cultured adherently growing luciferase-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 57 publications
3
45
1
1
Order By: Relevance
“…Ideally, alternative noninvasive strategies with minimal risks for the patient, high transplantation efficiency, and the possibility of a chronic treatment option are needed. Systemic intravascular application of cells could be another option, but major obstacles would be the entrapment and elimination of cells in peripheral organs and the risk of vascular and pulmonary embolization [10,14,29]. Although we detected NSPCs in the spleen after intranasal delivery indicating a systemic distribution we did not observe any NSPCs in lung or liver tissue at any time point.…”
Section: Discussioncontrasting
confidence: 56%
“…Ideally, alternative noninvasive strategies with minimal risks for the patient, high transplantation efficiency, and the possibility of a chronic treatment option are needed. Systemic intravascular application of cells could be another option, but major obstacles would be the entrapment and elimination of cells in peripheral organs and the risk of vascular and pulmonary embolization [10,14,29]. Although we detected NSPCs in the spleen after intranasal delivery indicating a systemic distribution we did not observe any NSPCs in lung or liver tissue at any time point.…”
Section: Discussioncontrasting
confidence: 56%
“…In the case of systemic injection of NSCtk for brain cancer therapy, the majority of intravenously injected cells became stuck in the lung and liver because of the narrow diameters of lung capillaries and liver sinusoids. 55 Damaging normal proliferating cells in these organs by the bystander effect of phosphorylated GCV is a major safety concern here. One possible way to alleviate this problem is to develop a new regulation system that triggers transgene expression in NSCs only after they home in on tumors.…”
Section: Hesc-derived Nscs and Glioma Gene Therapy Y Zhao Et Almentioning
confidence: 99%
“…The evaluation of neural cell distribution after intravenous cell transplantation has shown that most of the cells are initially entrapped within the lungs and do not travel to the brain. 3 It has been hypothesized that an intraarterial approach would be a more efficient route of cell delivery to the brain, as this approach avoids the pulmonary circulation. This approach is particularly attractive when selecting and sorting cells for adhesion molecules, which can enhance cell homing and therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%